COVID-19 Pandemic: Effect on Confidence Levels of Portuguese Towards People of Different Professions - Ricou M; Pereira T; Pereira HP; Picoli R; Marina S (Dove Medical Press, 2021)
Miguel Ricou,1,2 Tiago Pereira,3 Helena P Pereira,1,2 Ricardo Picoli,4 Sílvia Marina1,2 1Department of Community Medicine, Information and Decision in Health of the Faculty of Medicine of University of Porto, Porto, Portugal; 2Cintesis-Center for Health Technology and Services Research, Porto, Portugal; 3Order of Portuguese Psychologists, Lisbon, Portugal; 4Faculty of Philosophy, Science and Letters of Ribeirão Preto at University of Sao Paulo, Sao Paulo, BrazilCorrespondence: Sílvia MarinaDepartment of Community Medicine, Information and Decision in Health of the Faculty of Medicine of the University of Porto, Alameda Prof. Hernâni Monteiro, Porto, 4200-519, PortugalTel +351 919824713Email silviamarina@outlook.comBackground: The COVID-19 pandemic is emerging in a world where science is highly developed. Nevertheless, science is not the only resource that people resort to when they have difficulties. In this pandemic context, some professions became more relevant, including front-line professionals, such as medical doctors and nurses, and those who may have an indirect role. The aim of this study is to understand whether there is a strengthening of people's confidence, in politicians, journalists, science-based activities, and in more mystical dimensions.Methods: A cross-sectional study was carried out to understand the levels of confidence of the Portuguese population in several professional groups, measured in two pandemic moments. Participants were recruited to participate in the study through online platforms. The sample was randomly collected from the Portuguese population. The sample was composed of 1455 Portuguese people with a mean age of 44 years, and 1080 were female.Results: We found high levels of confidence in medical doctors and nurses, as well as in other health professions, science, and education. We detected the opposite trend for politicians and journalists. Measured in two pandemic moments, we found confidence levels in these professionals were lower in September than in July with statistical significance differences [(politicians (t = 3.15, p = 0.00); journalists (t = 2.49, p = 0.01)].Conclusion: It is important to improve a joint action between politicians, journalists, health and science professionals to communicate measures to increase confidence from people. There is a need for the engagement of the population in the adoption of protective measures and contribute to easier control in pandemic situations.Keywords: COVID-19, confidence interval, professions, cross-sectional study